A cascade palladium-mediated cross-coupling/electrocyclization approach to the construction of fused bi- and tricyclic rings. - Kan, S; Anderson, E (2008)
A versatile palladium-catalyzed cyclization/cross-coupling/electrocyclization strategy for the synthesis of fused bi- and tricyclic ring systems is described. Excellent yields of the polycyclic products are obtained with a range of tethering ring sizes and functionality, including an unprecedented 5,6,4,5-fused tetracycle. The reaction mechanism features two unusual palladium-mediated isomerizations prior to electrocyclization.